STUDI PEMBUATAN BAGIAN ALAT REHABILITASI PENDERITA STROKE DENGAN PENDEKATAN METODE TAGUCHI - Franando, Franando; Zamheri, Ahmad; Arifin, Fatahul (Politeknik Negeri Sriwijaya, Indonesia, 2020)
3D Printer is a solution to fulfill product demand that is custom design and not necessarily mass production. However, as long as the printing process produces a product that is not the same as the design size and has a fragile structure, there is a small deviation of dimensional accuracy and hardness value. This research focuses on dimensional accuracy and hardness of 3D Printer prints by using the design of one of the components of stroke rehabilitation tools, It aims to find a printing parameter component of a stroke rehabilitation tool that can have minimum dimensional accuracy and has a maximum hardness value. This study used Color Change Filament material for 3D printing with Taguchi data processing method and succeeded in reducing dimensional accuracy deviation with Layer Height percentage (52.225%), Print Speed of (15.432%) and Print Temperature amounting to (14.060%). The optimal process Parameter for obtaining the minimum dimensional accuracy is the 0.10 mm Layer Height of Print Speed 40 mm/s and the Print Temperature of 195 oC. Maximum hardness value with a Layer Height percentage of (26.015%), Print Speed (60.511%) and Print Temperature amounting to (8.213%). The optimal process Parameter for obtaining the maximum hardness value is the 0.10 mm Layer Height of the Print Speed of 20 mm/s and the Print Temperature of 205 oC.